2020
DOI: 10.1029/2019jb018582
|View full text |Cite
|
Sign up to set email alerts
|

Shear Velocity Model of Alaska Via Joint Inversion of Rayleigh Wave Ellipticity, Phase Velocities, and Receiver Functions Across the Alaska Transportable Array

Abstract: Through the Alaska Transportable Array deployment of over 200 stations, we create a 3‐D tomographic model of Alaska with sensitivity ranging from the near surface (<1 km) into the upper mantle (~140 km). We perform a Markov chain Monte Carlo joint inversion of Rayleigh wave ellipticity and phase velocities, from both ambient noise and earthquake measurements, along with receiver functions to create a shear wave velocity model. We also use a follow‐up phase velocity inversion to resolve interstation structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 85 publications
(203 reference statements)
17
87
0
1
Order By: Relevance
“…On average, there are ∼2,000 models in each posterior. Details about the number of iterations, avoiding the edges of prior distributions, and data uncertainties can be found in previous works (Berg et al, 2018(Berg et al, , 2020Shen et al, 2012).…”
Section: Monte Carlo Joint Inversionmentioning
confidence: 99%
“…On average, there are ∼2,000 models in each posterior. Details about the number of iterations, avoiding the edges of prior distributions, and data uncertainties can be found in previous works (Berg et al, 2018(Berg et al, , 2020Shen et al, 2012).…”
Section: Monte Carlo Joint Inversionmentioning
confidence: 99%
“…There are also seismic studies which investigated subducting zone structures using body wave tomography (e.g., Eberhart‐Phillips, et al., 2006; Gou et al., 2019), surface wave tomography (e.g., Berg et al., 2020; Feng et al., 2020; Feng & Ritzwoller, 2019; Jiang et al., 2018; Nayak et al., 2020; Wang & Tape, 2014; Y. Wang & Tape, 2014; Ward, 2015), receiver functions (e.g., Miller & Moresi, 2018; Zhang et al., 2019) and shear wave splitting (e.g., Hanna & Long, 2012; Venereau et al., 2019). Important isotropic structures, including the geometry of the subducting Pacific slab and the Yakutat microplate, are resolved by numerous seismic tomography studies (e.g., Berg et al., 2020; Feng & Ritzwoller, 2019; Gou et al., 2019; Jiang et al., 2018; Nayak et al., 2020). And the distribution of crustal radial anisotropy, which reflects the mid‐Cretaceous extensional deformation, is imaged by Feng and Ritzwoller (2019).…”
Section: Introductionmentioning
confidence: 99%
“…tropy studies showing a rotation of fast-axis directions around the Pacific slab (e.g., Venereau et al, 2019). Some seismic tomography models also support this hypothesis as they do not show a slab signature beneath the WVF (Berg et al, 2020;Martin-short et al, 2018). Therefore, questions remain regarding the detailed relationship between subduction and volcanism in the WVF in view of recent geophysical studies such as what controls the observed volcanism across the WVF?…”
mentioning
confidence: 99%